Thomas J. Fararo: The Meaning of General Theoretical Sociology: Tradition and Formalization - Kaspersen, Lars Bo (Tidsskriftet Antropologi, 1993)
Thomas J. Fararo: The Meaning of General Theoretical Sociology: Tradition and Formalization Anmeldes af Lars Bo Kaspersen